2008
DOI: 10.1007/s12038-008-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cytomixis on meiosis, pollen viability and pollen size in wild populations of Himalayan poppy (Meconopsis aculeata Royle)

Abstract: We report the occurrence of cytomixis in wild populations of Himalayan poppy (Meconopsis aculeata Royle),which is considered to be an important and threatened medicinal plant growing in the high hills of the Himalayas. The impact of cytomixis on meiotic behaviour, reduced pollen viability and heterogeneous-sized pollen grains was also studied. Cytological studies in the seven wild populations from the high hills of Himachal Pradesh revealed that all the Himalayan populations exist uniformly at the tetraploid l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
69
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 40 publications
(40 reference statements)
23
69
0
2
Order By: Relevance
“…Most of these observations are in line with the findings of Ghaffari (2006) and Singhal et al (2008) in some of the species of angiosperms. The present findings reveal that cytomixis may be responsible for a high rate of meiotic abnormalities coupled with the production of hypo-and hyperploid chromosome numbers in some PMCs in this species ultimately resulting in the formation of low apparently fertile pollen grains of variable sizes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most of these observations are in line with the findings of Ghaffari (2006) and Singhal et al (2008) in some of the species of angiosperms. The present findings reveal that cytomixis may be responsible for a high rate of meiotic abnormalities coupled with the production of hypo-and hyperploid chromosome numbers in some PMCs in this species ultimately resulting in the formation of low apparently fertile pollen grains of variable sizes.…”
Section: Discussionsupporting
confidence: 91%
“…This phenomenon has been seen in many of the angiospermic plant species with different possible causes being advocated as physiological conditions, stress factors or purely under genetic control. However, in the present material, the cytomixis seems to be under genetic control as pointed out earlier by other researchers (Bellucci et al 2003, Singhal et al 2008. On the basis of these detailed cytomorphological studies, it is concluded that F. vestita represents single diploid taxon with n=7 but showing the well-marked, completely identified and segregated 2 additional morphovariants (Type-II and Type III) in addition to the existing 2 variants reported from the Western Himalayas.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, in the current study, such gametes could not be ascertained. Non-synchronous disjunction of bivalents is either found in hybrid taxa or the species having structural differentiation between the homologous pair and rate of terminalization (Singhal 1982, Anis and Wani 1997, Aparicio and Albaladejo 2003, Wang et al 2004, Bhat et al 2007, Wen et al 2010 or associated with other meiotic abnormalities (Singhal and Kumar 2008. The occurrence of non-synchronous disjunction of bivalents in the asymmetric somatic hybrids of Brassica napus and Crambe abyssinica had been attributed to a type of asynchrony in the meiotic cycles between genomes of hybrid species by Wang et al (2004).…”
Section: Resultsmentioning
confidence: 99%
“…Presumably, their fundamental role is in the transfer of part of genetic material from one cell to another via cytomixis resulting in an increase in genetic diversity of the produced pollen or an adjusting and balancing in unbalanced genomes (Falistocco et al 1995;Zhou 2003;Ghaffari 2006;Lattoo et al 2006;Negron-Ortiz 2007;Singhal and Kumar 2008;Song and Li 2009;Singhal et al 2011).…”
Section: Causes and Consequencesmentioning
confidence: 99%